1998
DOI: 10.1126/science.279.5354.1159
|View full text |Cite
|
Sign up to set email alerts
|

Fixing Mismatches

Abstract: among species and populations can be understood as adaptations. But at some stages of evolution certain characters effectively "click in" and remain fixed in the descendent group of species (5-7). For instance, And the impact of repair machinery on the quentially during clonal expansion, and the H, clarke J, Exp, Med, 161, 687 (1985).immune response needs clarification. Indeed, influence of selection is seen by the distribu-6. D. J. McKean eta/., J. k p . Med. 161,687 (1985). there is a discrepancy between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This degeneracy in antigen recognition is typically associated with low-affinity interactions and is a hallmark of the preimmune B lymphocyte repertoire. It is via the processes of somatic mutation of B cell receptors and selection of antigen-reactivated B cells within germinal centers that B cell responses improve in both their affinity and fidelity for antigen recognition (12)(13)(14)(15)(16). This transition is paralleled by dramatic increases in both the association rate of the antigen-binding reaction and the structural rigidity of the receptors' antigen-binding site (9,17).…”
Section: Introductionmentioning
confidence: 94%
“…This degeneracy in antigen recognition is typically associated with low-affinity interactions and is a hallmark of the preimmune B lymphocyte repertoire. It is via the processes of somatic mutation of B cell receptors and selection of antigen-reactivated B cells within germinal centers that B cell responses improve in both their affinity and fidelity for antigen recognition (12)(13)(14)(15)(16). This transition is paralleled by dramatic increases in both the association rate of the antigen-binding reaction and the structural rigidity of the receptors' antigen-binding site (9,17).…”
Section: Introductionmentioning
confidence: 94%
“…Quite astonishingly, while antibody diversification is perturbed by single deficiency in either UNG or MSH2, combined UNG/MSH2 deficiency completely abolishes switch recombination and hypermutation at dA:dT pairs [51]. Finally, mice mutant for EXO1, which participates in MMR as described above, have changes similar to those in MSH2-deficient mice [52].Previously, we suggested that MMR is co-opted in hypermutation by actively fixing mutations rather than repairing them, which may involve additional B cellspecific factors [23,42]. Here we analyze the influence of mismatch repair on hypermutation in non-B cells that ectopically express AID.…”
mentioning
confidence: 89%
“…Previously, we suggested that MMR is co-opted in hypermutation by actively fixing mutations rather than repairing them, which may involve additional B cellspecific factors [23,42]. Here we analyze the influence of mismatch repair on hypermutation in non-B cells that ectopically express AID.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations